Pengetahuan Ibu Hamil dalam Mengkonsumsi Tablet Fe - Sri Andayani (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Anemia is the biggest public health problem, especially in the group of women of childbearing age (WUS). According to WHO, the global prevalence of anemia in pregnant women worldwide is 41.8%. One of the causes of anemia in pregnantcy is parity and age of the mother. Anemia in pregnancy can occur due to several events including nutrition of pregnantcy, adherence to taking Fe tablets, pregnancy disorders, maternal parity, and other things which are also caused by lower education levels and lack of knowledge of mothers about the dangers of anemia in pregnancy. This study aims to determine the knowledge of pregnantcy consuming Fe tablets.This research is a type of analytical research, with a cross design sectional. The total population is 40 respondents, the sampling technique is total sampling. The research instrument was the knowledge of pregnantcy in consuming Fe tablets. Data analysis used the Chi-square statistical test. The results of this study indicate that most of the respondents (47.5%) have good knowledge about the correctness of consuming tablets Fe.